1978
DOI: 10.1029/ja083ia06p02552
|View full text |Cite
|
Sign up to set email alerts
|

The role of field‐aligned ionization irregularities in the generation of the HF‐induced plasma line at Arecibo

Abstract: By using the data from the July 1976 ionospheric modification experiments at Arecibo it was discovered that the Langmuir waves responsible for the enhanced plasma line are generated at the height in the ionosphere at which the Airy function, which describes the standing electric field of the high‐frequency (HF) modifying wave near reflection, has its main maximum. It would be impossible for the enhanced Langmuir waves which backscatter the 430‐MHz radar signal to exist at this height in a uniformly varying ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“… Gurevich et al [2002] suggested that decreased plasma densities within striations generated by heating waves permit necessary phase matching [cf. Muldrew , 1978]. Changes in the refraction index (self‐focusing) due to striations develop within tens of seconds after turn‐on and explain some features of the spatial distribution of the HF‐induced airglow.…”
Section: Introductionmentioning
confidence: 99%
“… Gurevich et al [2002] suggested that decreased plasma densities within striations generated by heating waves permit necessary phase matching [cf. Muldrew , 1978]. Changes in the refraction index (self‐focusing) due to striations develop within tens of seconds after turn‐on and explain some features of the spatial distribution of the HF‐induced airglow.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion equations used are valid for a homos:eneons plasma. Although striations are present and may affect the waves propagation [Muldrew, 1978], the plasma is assumed to be locally homogeneous so that the model gives useful information on the waves dispersion properties.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma line from this height is usually several orders of magnitude stronger than that from the lower height corresponding to the backscatter resonance condition in a medium in which the irregular structure perpendicular to B has been averaged out. By ray tracing of trapped plasma waves in the vicinity of the pump Airy maximum, Muldrew [1978] finds a substantial parametric amplification of obliquely propagating waves. At some point of the ray path the wave vector may make a 45 ø angle to B and may thereby cause direct backscatter of the probing wave at Arecibo.…”
Section: Introductionmentioning
confidence: 99%